Kinerja Penyuluh Pertanian Lapangan (PPL) dan Kaitannya terhadap Pendapatan Usahatani Padi di Kabupaten Banyuasin - Idham Alamsyah; Henny Malini; Desi Aryani (Seminar Nasional Lahan Suboptimal, 2018)
Alamsyah et al, 2019. Performance of the Field Agriculture Intructors (PPL) and the Relationship to Farming  Income in Banyuasin District. pp. 313-321. The performance of extension workers in this study was by the level of satisfaction of farmers who received agricultural extension services. This research was carried out in Banyuasin Regency. This reasearch aimed was to analyze performance of the field agriculture intructors (PPL) and the relationship to farming  income in Banyuasin District.  Primary and secondary data collection is carried out in May to July 2018. Implementation of activities includes collection of secondary data and primary data. The sample withdrawal method is done with a simple random sampling method. The results showed that the performance of PPL in Banyuasin District had a score of 22.48 which means that the performance of PPL was good enough, PPl performance was seen from 4 indicators, namely planning, implementation and evaluation. Planning has a score of 5.43 which means that it is not good, when the farmer makes his farming plan for the next planting season PPL does not accompany the farmer, so that the farmers lack guidance in planning their farming, the implementation score has a score of 8.48 which means the performance of the instructor Field agriculture is quite good, because during the growing season PPL visits farmers and provides guidance, and for evaluation indicators that is equal to 8.58, which means that the performance of PPL in conducting supervision and evaluation of farmer farming is good enough. The results of the data analysis there is an unreal relationship between PPL performance and income.